Physical characterisation of microporous and nanoporous polymer films by atomic force microscopy, scanning electron microscopy and high speed video microphotography. Issue 4 (2004) - Barrow Barrow, M. S. M. S.; Jones Jones, R. L. R. L.; Park Park, J. O. J. O.; Srinivasarao Srinivasarao, M. M.; Williams Williams, P. R. P. R.; Wright Wright, C. J. C. J.
Abstract : We report studies of ordered microporous and nanoporous polymer films formed by the evaporation of polymer solutions following exposure to a humid atmosphere. High speed microphotographic (HSMP) studies of the formation process showed that near the surface of the polymer solution, vapour condensation produced near mono-disperse water droplets which form a close-packed monolayer (or 'breath figure'). Following the evaporation of the solvent, characterisation of the solid by Atomic Force Microscopy and Scanning Electron Microscopy revealed that the surface of the polymer film is characterised by extensive regions of hexagonally close-packed microscopic pores, whose spatial arrangement replicates that of the initial droplet monolayer. Characterisation of sections of the film by Atomic Force Microscopy established that the surficial pores represent open sections of sub-surficial spheroidal cavities formed by encapsulation of the water droplets within the polymer solution. An interesting feature of the results is the occurrence of nano-scale pores at the film surface and at (and within) the walls of the sub-surficial microscopic pores. This is the first physical evidence report of such features in porous polymer films produced by a process involving breath-figures. Their dimensions suggest that more detailed structural investigations will require alternative techniques to conventional, optical methods.